Engaging with faith groups to prevent VAWG in conflict-affected communities: results from two community surveys in the DRC - Elisabet Le Roux; Julienne Corboz; Nigel Scott; Maggie Sandilands; Uwezo Baghuma Lele; Elena Bezzolato; Rachel Jewkes (BMC, 2020)
Abstract Background An evaluation was conducted of a three-year intervention focused on violence against women and girls (VAWG) and implemented in the conflict-affected north-east of the Democratic Republic of Congo (DRC), a country with high rates of VAWG. The intervention addressed VAWG, and especially sexual violence, by specifically engaging with communities of faith and their leaders. Methods Two community surveys were conducted, one before and one after the intervention, in three health areas in Ituri Province in the DRC. At both baseline and endline, data was collected from male and female members of randomly selected households in 15 villages (five per health area) in which the intervention was being implemented. At baseline the sample comprised 751 respondents (387 women, 364 men) and at endline 1198 respondents (601 women, 597 men). Questionnaires were interviewer-administered, with sensitive questions related to experience or perpetration of violence self-completed by participants. Results The study showed significantly more equitable gender attitudes and less tolerance for IPV at endline. Positive attitude change was not limited to those actively engaged within faith communities, with a positive shift across the entire community in terms of gender attitudes, rape myths and rape stigma scores, regardless of level of faith engagement. There was a significant decline in all aspects of IPV in the communities who experienced the intervention. While the experience and perpetration of IPV reported at endline did not track with exposure to the intervention, it is plausible that in a context where social norm change was sought, the impact of the intervention on those exposed could have had an impact on the behaviour of the unexposed. Conclusion This intervention was premised on the assumption that faith leaders and faith communities are a key entry point into an entire community, able to influence an entire community. Research has affirmed this assumption and engaging with faith leaders and faith communities can thus be a strategic intervention strategy. While we are confident of the link between the social norms change and faith engagement and project exposure, the link between IPV reduction and faith engagement and project exposure needs more research.